Legal Politics of Combating Thuggery In the Perspective of Critical Criminology and Islamic Law - Siagian, Amrizal; Yunus, Nur Rohim; Raihani, Fina; Setiawan, Refly (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
Phuggery is a form of social crime that disturbs society and often arises due to economic inequality, social marginalisation, and weak structural policies to overcome it. In practice, the state's legal response to thugs tends to focus on a repressive and symbolic approach through law enforcement and criminalisation operations alone, without touching on the more complex roots of the problem. This study aims to examine the direction and strategy of Indonesian legal politics in addressing the phenomenon of thugs and to analyse alternative policies based on critical criminology and Islamic legal values. The research method employed is a normative qualitative approach with a conceptual and comparative focus. Data sources comprise primary legal materials, such as laws, police regulations, the Qur'an, and hadith, as well as secondary legal materials, including books, scientific journals, interpretations, and criminology literature. The analysis was conducted descriptively and critically, utilizing the theoretical framework of critical criminology and fiqh al-jinayah (Islamic criminal law). The results of the study indicate that thugs cannot be overcome only with the coercive power of the state, but instead require a structural and ethical approach that supports social justice. Critical criminology critiques the labelling of the lower class, while Islamic law emphasises the principles of ta’zīr, correction (islāh), and preventive justice. Thus, integrating critical criminology approaches and Islamic values ​​can be the basis for a more humanistic and sustainable legal policy reform. Keywords: Legal Politics; Thuggery; Critical Criminology; Islamic Law; Social Justice